Theoretical and practical aspects of the relationship between the balance of the payment and the exchange rate - Елемесов, Р.; Хамзаева A. (Journal of Economic Research & Business Administration, 2017)
In the context of global economic integration increases the exchange of goods and services, as well as increased capital flows between countries. As a result, formed and developed the international currency market, where the established exchange rates of various currencies. The transition to floating exchange rates has caused the need for a radical revision of views on the balance of payments and the exchange rate, the nature of their formation, and changes in, the relationship with other economic variables, methods of state and interstate regulation. Exchange rate changes have a significant impact on the balance of trade and the movement of capital, which ultimately affects the state of the country’s balance of payments. The balance of payments is an important indicator and a tool to predict the extent possible the country’s participation in world trade, international economic relations, to establish its solvency. Therefore, the relationship of the exchange rate and balance of payments is one of the most important problems of economic analysis, both theoretical and practical aspects.